The De-Provisioning Gap in Identity Management for Agentic AI - Jablonski, Fernanda Lauck; Müller, Fernanda L.; Sant Ana, Julio Ribeiro; Schoenardie, Yuri H. Lima; Silva, Kléber H. Cardoso da; Schardong, Frederico (Anais Estendidos do Simpósio Brasileiro de Cibersegurança (SBSeg), 2026)
Various proposals have emerged to address challenges related to identity, authentication, and authorization in agentic systems. Given this context, this article compiles key proposals, such as OIDC-A, SPIFFE, A-JWT, A2A, and LDP, and compares them based on five criteria derived from the “Identity Management for Agentic AI” white paper. The results show that, although current proposals are robust in specific areas, none satisfies all analyzed criteria. The main limitation is the lack of rapid, verifiable de-provisioning, highlighting challenges in the reliable revocation of identities and permissions in agentic AI.